Accessory Extraocular Muscle as a Cause of Restrictive Strabismus. (1st October 2016) - Molinari, A.; Plager, D.; Merino, P.; Galan, M. M.; Swaminathan, M.; Ramasuramanian, S.; de Faber, J. T. H. N.
ABSTRACT: Restrictive strabismus resulting from the presence of an accessory extraocular muscle has rarely been reported in the literature. Most articles written on this topic are isolated case reports. The purpose of this paper is to describe a series of 7 similar patients presenting with atypical restrictive strabismus associated with enophthalmos in the affected eye, which was found to be caused by an accessory extraocular muscle attached to the posterior globe near the optic nerve. The medical records of 7 patients who shared these clinical characteristics were retrospectively analyzed. Orbital imaging was obtained in the 7 cases, which were compared. Three of the patients were females and four were males. The left eye was affected in all 4 males and the right eye was affected in the 3 females. The 7 patients presented with the following clinical characteristics: enophthalmos, restriction to eye movements in most fields of gaze, and presence of an anomalous orbital structure that was interpreted on magnetic resonance imaging (MRI) to be an accessory extraocular muscle inserting onto the posterior surface of the globe in the affected eye. The fellow eye was normal in all cases. Five of the 7 patients underwent surgical correction with partial improvement in only one patient. The presence of an accessory extraocular muscle should be included in the differential diagnosis of patients with atypical restrictive strabismus. Orbital computed tomography or MRI are essential for correct diagnosis in these cases.